Mathematical Modeling on Aligned Magnetic Field of Two-Phase Dusty Casson Fluid - N. S., Arifin; S. M., Zokri; L. A., Aziz; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh; N. F., Mohammad (Centre for Advanced Research on Energy (CARe), 2017)
The influence of aligned magnetic field on the two-phase flow of Casson f1uid and dust particle with heat transfer over a stretching sheet subjected to convective boundary conditions (CBC) is analysed. The governing equations are transformed into ordinary differential equations by employing similarity transformation which then solved numerically by runge4 Kutta Fehlberg fourth-fifth method (RKF45). The effects of aligned angle and fluid particle interaction parameter are presented graphically for both phases by fixing several physical parameters. It has been found that aligned angle strengthens the magnetic field and led to decrease the velocity profile for both phases.